Energodynamic Field Theory (Global Journal of Science Frontier Research, 2021)
The article proposes a theory of a unified force field, based on the recognition of the inevitability of oscillations in the inhomogeneous density field of the "primary" form of matter ("prematter"), which was previously called ether. It is shown that the energy of these oscillations is equal to the product of the mass involved in this motion by the square of the speed of light, and the inhomogeneity of its distribution generates an all-pervading gravitational field proportional to the density gradient of the pre-matter. The corresponding short-range (field) form of the law of gravity is found, which reveals that gravity belongs to the most "strong" interactions and predicts the appearance of both attraction and repulsion forces in continuous media.
Keywords: unified field theory; the nature of gravity and electromagnetism; the laws of newton and coulomb